2008
DOI: 10.1111/j.1529-8817.2007.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

MICROALGAL BIOTRANSFORMATION OF STEROIDS1

Abstract: Microbial biotransformation of steroids is not a new concept, but most studies in this field have focused on fungal and bacterial systems. Microalgae, despite their photosynthetic ability and immense biodiversity, have not received much attention in this aspect until recently. Since the publication of the first article on microalgal biotransformation of steroids about 20 years ago, there have been many reports describing different modifications, including hydroxylation, reduction, side-chain degradation, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 66 publications
0
20
0
1
Order By: Relevance
“…1). It has already been shown that some bacterial, fungal and algal species are capable of performing various transformations on pregnane-based compounds (Faramarzi et al 2008;Mahoto and Mukherjee 1984). The present work shows that M. tenera is able to convert progesterone into four steroid metabolites.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…1). It has already been shown that some bacterial, fungal and algal species are capable of performing various transformations on pregnane-based compounds (Faramarzi et al 2008;Mahoto and Mukherjee 1984). The present work shows that M. tenera is able to convert progesterone into four steroid metabolites.…”
Section: Resultsmentioning
confidence: 81%
“…The first application of cyanobacteria in biotransformation of steroids goes back to 1986 when Abul-Hajj and Qian (1986) studied the ability to convert steroids using different algal strains. Since then, many studies on this feature of microalgae have been performed and a variety of products have been obtained (Faramarzi et al 2008). Currently, steroids and their derivatives have been found extensive applications, such as anabolic, hormone replacement, progestational, antitumor agents, and oral contraceptives as well as sedatives.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of N. muscorum (and most other cyanobacteria) to grow in mineral media containing no organic nutrients both reduces production cost and minimizes the risk of contamination by other microorganisms in fermentation processes (Faramarzi et al 2008;Hajimahmoodi et al 2009). Some important enzymes including hydrogenase (Tamagnini et al 2002) and ornitine transcarbamoylase (Wolk et al 1994) have been isolated from this microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…Whole cell biocatalysis using fungi, bacteria, and algae has been extensively applied in steroid biotransformations over the last half century [1][2][3]. The ability of microorganisms to introduce functional groups into chemically inactive carbons of complex molecules has made microbial transformations an indispensable part of the manufacturing process of most pharmaceutically important steroids.…”
mentioning
confidence: 99%